1999
DOI: 10.1021/jf9808527
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Sparkling Wines (Cavas) As Inhibitors of in Vitro Human Low-Density Lipoprotein Oxidation

Abstract: Forty-seven dealcoholized sparkling wines (cava) from the Penedès area in Spain were tested for their antioxidant activity in a low-density lipoprotein system. The effect of different quality-related parameters, such as harvest year or grape variety, was investigated. Twenty-two phenolic compounds were separated by high-performance liquid chromatography and identified by comparing their retention time and their ultraviolet spectra with those of pure standards. When tested at the same total phenol concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
(31 reference statements)
2
20
1
Order By: Relevance
“…Poor correlation coefficients for DPPH and flavonols, and for DPPH and total hydroxicinnamic esters were found in white wines (De Beer and others 2003). In a study with 47 sparkling wines, total hydroxycinnamates did not show correlation with the antioxidant activity in low‐density lipoprotein system, while the flavonol quercitin 3‐glucuronide showed a limited correlation (Satué‐Gracia and others 1999). …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Poor correlation coefficients for DPPH and flavonols, and for DPPH and total hydroxicinnamic esters were found in white wines (De Beer and others 2003). In a study with 47 sparkling wines, total hydroxycinnamates did not show correlation with the antioxidant activity in low‐density lipoprotein system, while the flavonol quercitin 3‐glucuronide showed a limited correlation (Satué‐Gracia and others 1999). …”
Section: Resultsmentioning
confidence: 95%
“…Insufficient information has been reported concerning the antioxidant characteristics of sparkling wines. The antioxidant activity of sparkling wines toward low‐density lipoprotein oxidation has been correlated with the total phenolic content and other individual phenolic compounds (caffeic acid, coumaric acid, protocatechic acid, quercetin 3‐glucuronide) (Satue‐Gracia and others 1999). Moreover, it has been suggested that the role of phenolic compounds is greater in the antioxidant activity of the sparkling wines made by the Champenoise method than in those elaborated with the Charmat method (Stefenon and others 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant properties of grape beverages have been shown to protect LDLs from oxidative modifications. 47,51,52 In fact, Napoli et al 4 demonstrated that administration of antioxidants from wine in experimental models diminished the severity of atherosclerosis by reducing oxidative stress and increasing cNO production.…”
Section: Discussionmentioning
confidence: 99%
“…ranging from 0.1 to 1.2 mg L À1 (Satue´-Gracia, Andre´s-Lacueva, Lamuela-Ravento´s and Frankel, 1999). Further, in seven Spanish wines made from Malvar, Verdejo, Albillo, and Chardonnay, total flavonol concentration varied from 2 to 7 mg L À1 , the average being 4.29 mg L À1 .…”
Section: Article In Pressmentioning
confidence: 96%